The invisible woman - Patterson, James, 1947-; DiLallo, Susan, 1947- (Little, Brown and Company, 2026)
"Elinor Gilbert was once a young woman with a thriving career at the FBI. Now decades past solving crimes with the bureau, she is personally and professionally forgettable--which is exactly what her former FBI boss needs. He disguises Elinor as a middle-aged nanny, and casts her as an agent on the inside of his investigation into a New York art dealer suspected of ties to organized crime. But as Elinor pushes toward the truth, her superpower--anonymity--morphs into a fatal flaw. The more the invisible woman integrates into her 'host' family, the more dangerously memorable she becomes"--